2019
DOI: 10.1200/jco.18.01842
|View full text |Cite
|
Sign up to set email alerts
|

NAB-Paclitaxel Improves Disease-Free Survival in Early Breast Cancer: GBG 69–GeparSepto

Abstract: PURPOSE The GeparSepto trial demonstrated that weekly nanoparticle albumin-bound (NAB)–paclitaxel significantly improves the pathologic complete remission rate compared with weekly solvent-based (sb) paclitaxel followed by epirubicin plus cyclophosphamide as neoadjuvant treatment in patients with primary breast cancer (BC). Here, we report data on long-term outcomes. METHODS Patients with histologically confirmed primary BC were randomly assigned in a 1:1 ratio to 12 times weekly NAB-paclitaxel 150 mg/m2 (afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 25 publications
4
90
0
10
Order By: Relevance
“…When nab-paclitaxel was used instead of paclitaxel in phase III trial, the improvement of pCR was not statistically significant, showing pCR 41.3% with nab-paclitaxel vs. 37.7% with paclitaxel in the TNBC group (OR 0.85; 90% CI, 0.49-1.45) [52]. The GeparSepto trial that included about 20% of TNBC demonstrated significantly higher pCR in nab-paclitaxel subgroup than in the paclitaxel subgroup (48% vs. 26%, p = 0.00027) [53]. Additionally, nab-paclitaxel showed superior pCR when given with carboplatin as compared with gemcitabine [44].…”
Section: Platinum In Tnbcmentioning
confidence: 96%
“…When nab-paclitaxel was used instead of paclitaxel in phase III trial, the improvement of pCR was not statistically significant, showing pCR 41.3% with nab-paclitaxel vs. 37.7% with paclitaxel in the TNBC group (OR 0.85; 90% CI, 0.49-1.45) [52]. The GeparSepto trial that included about 20% of TNBC demonstrated significantly higher pCR in nab-paclitaxel subgroup than in the paclitaxel subgroup (48% vs. 26%, p = 0.00027) [53]. Additionally, nab-paclitaxel showed superior pCR when given with carboplatin as compared with gemcitabine [44].…”
Section: Platinum In Tnbcmentioning
confidence: 96%
“…A number of HMW-based therapeutic strategies has been clinically approved and proposed for the therapy of advanced breast cancer, pancreatic ductal denocarcinoma and other tumors, including albumin-bound drug conjugates, such as nanoalbumin bound paclitaxel, nAb-PTX or Abraxane R (Blomstrand et al, 2019;Li and Kwon, 2019;Untch et al, 2019), monoclonal antibodies (mAb), such as anti-HER2 mAb trastuzumab (Figueroa-Magalhaes et al, 2014) or anti-EGFR mAb, cetuximab (Huang and Buchsbaum, 2009), and genetic materials, including siRNA, mRNA, and aptamers (Kang et al, 2015;Ngamcherdtrakul and Yantasee, 2019). In liver metastatic lesions with low vascularization patterns, these potent therapeutics are unable to be transported deeply enough into the lesions prior to their clearance from circulation.…”
Section: Challenges For Nanotherapy In the Tumor Microenvironmentmentioning
confidence: 99%
“…The improvement of pCR rate was mainly observed among the 275 patients affected by TNBC (48% with nab-paclitaxel versus 26% with standard paclitaxel). Noteworthy, a significant invasive DFS benefit was reported in the TNBC subgroup who achieved pCR, supporting the value of pCR as the surrogate endpoint for long-term outcomes in this population [87].…”
Section: Taxanesmentioning
confidence: 57%